Dialogues of South American Archaeology: Hermann von Ihering, the Paulista Museum and the Argentine museums at the end of nineteenth century and beginning of twentieth century - Ferreira, Lúcio Menezes (Revista do Museu de Arqueologia e Etnologia, 2009)
The paper aims at demonstrating that the archaeological views of Hermann von Ihering were the result of his exchanges with Argentinian scholars. As the first director of the Paulista Museum, São Paulo, Brazil, von Ihering, thanks to his interaction with several colleagues, was able to set up colonial policies in Brazil and beyond.